Pengaruh dan Efektivitas Maggot Sebagai Proses Alternatif Penguraian Sampah Organik Kota di Indonesia - Nurcholis Salman; Estin Nofiyanti; Tazkia Nurfadhilah (Fakultas Teknik, 2020)
One of the organic waste treatment using the bioconversion process of the Black Soldier Fly larvae or commonly called Maggot. This study aims to determine the total amount of waste produced from bioconversion and to determine the effect of variable type of waste on Maggot growth. The types of samples used are household waste, melon waste, chicory waste and tofu waste as a control. The research method uses the True Experimental Design method with the Posttest Only Control Design research design. The study began with hatching of 1 gram Black Soldier Fly eggs which were then incubated for four days. Analysis of the study was conducted when Maggot was 7 days old with the number of feeding varied per feed. The results showed that total organic waste decomposed varied in each sample, namely the average total waste of 8122.1 grams, 1859.7 grams, 1320.3 grams and 1683.3 grams. The percentage of waste showed 74.6% for samples without mashed and 87.1% for mashed samples. The type of waste gives a significant influence on the growth of Maggot the value of sig. 0.024 (sig. P value sig. Value)